2022
DOI: 10.1093/ofid/ofac348
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Reinfection in People With HIV in Taiwan After Achieving Sustained Virologic Response With Antiviral Treatment: The RECUR Study

Abstract: Background Data on hepatitis C virus (HCV) reinfection in East Asian people living with human immunodeficiency virus (HIV) after treatment-induced sustained virologic response (SVR) are limited. Methods HIV/HCV-coinfected patients in Taiwan who achieved SVR12 with interferon (IFN) or direct-acting antivirals (DAAs) between 2005 and 2021 underwent HCV RNA measurements at SVR24 and then biannually. HCV reinfection was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…In this international cohort composed predominantly of GBM with HIV from high-income countries, high reinfection incidence was observed among people treated for recent HCV infection, two to three times greater than contemporary reinfection estimates among at-risk populations treated for chronic HCV [8,9,15–17]. Reinfection was associated with a previous diagnosis of HCV reinfection, injection drug use posttreatment, condomless anal intercourse with casual male partners and geographic region.…”
Section: Discussionmentioning
confidence: 82%
“…In this international cohort composed predominantly of GBM with HIV from high-income countries, high reinfection incidence was observed among people treated for recent HCV infection, two to three times greater than contemporary reinfection estimates among at-risk populations treated for chronic HCV [8,9,15–17]. Reinfection was associated with a previous diagnosis of HCV reinfection, injection drug use posttreatment, condomless anal intercourse with casual male partners and geographic region.…”
Section: Discussionmentioning
confidence: 82%
“…In low-risk general patients with HCV who achieve SVR12 with antiviral treatment, the risk of HCV reinfection ranges from 0.14 to 0.185 per 100 PYs. [114][115][116] In PLWH, the risk of HCV reinfection was much higher (3.76 per 100 PYs) according to a recent meta-analysis. PLWH MSM and those with recent drug use had an incidence of reinfection of 6.01 and 5.49 per 100 PYs, respecitvely.…”
Section: Treatment Of Hcv Reinfectionmentioning
confidence: 99%
“…In low-risk general patients with HCV who achieve SVR 12 with antiviral treatment, the risk of HCV reinfection ranges from 0.14 to 0.185 per 100 PYs [ 114 - 116 ]. In PLWH, the risk of HCV reinfection was much higher (3.76 per 100 PYs) according to a recent meta-analysis.…”
Section: Treatment With Ifn-free Daasmentioning
confidence: 99%
“…Improved HCV screening and scale-up of HCV treatment are also important for reducing the risk of HCV re-infection amongst PLHIV [56]. A recent study of HCV re-infection among an adult PLHIV cohort in Taiwan found that those living with HIV had higher HCV re-infection rates than the HIV-negative reference population, and that HCV reinfection incidence increased following the availability of DAAs in the country, further highlighting the importance of post HCV treatment surveillance among PLHIV [57].…”
Section: Plos Onementioning
confidence: 99%